Correction: Cotton-like micro- and nanoscale poly(lactic acid) nonwoven fibers fabricated by centrifugal melt-spinning for tissue engineering. Issue 13 (12th February 2018) - Zhou, Hongli; Tang, Yufeng; Wang, Zongliang; Zhang, Peibiao; Zhu, Qingsan
Abstract : Correction for 'Cotton-like micro- and nanoscale poly(lactic acid) nonwoven fibers fabricated by centrifugal melt-spinning for tissue engineering' by Hongli Zhou et al., RSC Adv., 2018, 8, 5166–5179.